2016
DOI: 10.1016/j.eats.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Tenodesis: A Secure Fixation Technique for Biceps Long Head Tendinopathy During Arthroscopic Rotator Cuff Repair Using a Suture-Bridge Technique

Abstract: Tendinopathy of the long head of the biceps is often found as an intra-articular pathology in the glenohumeral joint. Because long head of the biceps lesions are common, surgical intervention to properly manage the long head of the biceps has become an important issue. Both tenodesis and tenotomy have been shown to provide benefits in biceps long head tendinopathy. But because of concerns about muscle power reduction, cramping, and "Popeye's deformity," which may result from biceps tenotomy, biceps tenodesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been reported that LHBT tenotomy and LHBT tenodesis achieve satisfactory efficacy. As compared with LHBT tenodesis, pure LHBT tenotomy has the advantages of simplicity, short surgery time and rapid post-operative recovery (21,32,33), but it may cause complications including Popeye sign deformity (21,24,25,28), upper arm spastic pain, loss of stability of the humeral head (34)(35)(36) and reduced forearm supination strength (20,22,23). LHBT tenodesis is a more invasive surgical procedure, but it maintains the length and tension of the original tendon and the strength of the elbow muscle, effectively prevents muscle atrophy and minimizes spastic and Popeye sign deformity in the upper arm (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LHBT tenotomy and LHBT tenodesis achieve satisfactory efficacy. As compared with LHBT tenodesis, pure LHBT tenotomy has the advantages of simplicity, short surgery time and rapid post-operative recovery (21,32,33), but it may cause complications including Popeye sign deformity (21,24,25,28), upper arm spastic pain, loss of stability of the humeral head (34)(35)(36) and reduced forearm supination strength (20,22,23). LHBT tenodesis is a more invasive surgical procedure, but it maintains the length and tension of the original tendon and the strength of the elbow muscle, effectively prevents muscle atrophy and minimizes spastic and Popeye sign deformity in the upper arm (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…For example, keyhole xation may fail due to low primary stability [34], knot pullout [35], and excess tension [36]. The interference screw technique may lead to screw loosening [37] and tendon concis [32] because of proximal cancellous bone and tendon-bone extrusion [32], and the length-tension relationship is di cult to control with this technique [38,39]. The traditional single anchor xation technique may not offer adequate stabilization of the tendon, and the construct strength may be poor.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes, cosmesis, and structural integrity appear to be greater with bony suture anchor fixation 29 . Park et al 24 recently described a technique of combined bony and soft tissue tenodesis by suturing the tendon to the rotator interval in addition to placing a separate suprapectoral suture anchor in the bicipital groove. Lee et al 15 reported decreased pain and increased ASES and Constant scores in 84 patients undergoing suture anchor tenodesis in the bicipital groove in the setting of RCR.…”
Section: Discussionmentioning
confidence: 99%